Lemon-derived nanoparticle-functionalized hydrogels regulate macrophage reprogramming to promote diabetic wound healing - Enyou Jin; Yusheng Yang; Shengjie Cong; Dengke Chen; Ruixiong Chen; Jun Zhang; Yanjun Hu; Weini Chen (Journal of Nanobiotechnology)
Abstract The orderly regulation of immune inflammation and promotion of the regeneration of skin vessels and fibers are key to the treatment of diabetic skin injury (DSI). Although various traditional polypeptide biological dressings continue to be developed, their efficacy is not satisfactory. In recent years, plant-to-mammal regulation has provided an effective approach for chronic wound management, but the development of effective plant-based treatments remains challenging. The development of exosomes from Chinese herbs is promising for wound healing. In this study, plant exosomes derived from lemons (Citrus limon) were extracted, and their biological efficacy was verified. Lemon exosomes regulated the polarization reprogramming of macrophages, promoted the proliferation and migration of vascular endothelial cells and fibroblasts, and thus promoted the healing of diabetic wounds. To solve the problems of continuous drug delivery and penetration depth, Lemon Exosomes were loaded into a hydrogel constructed of Gelatin Methacryloyl (GelMA) and Dialdehyde Starch (DAS) that closely fits to the skin, absorbs water, swells, and is moist and breathable, effectively promoting the sustained and slow release of exosomes and resulting in excellent performance for diabetic wound healing. Our GelMA-DAS-Lemon Exosomes hydrogel (GelMA/DAS/Exo hydrogel) patch represents a potentially valuable option for repairing diabetic wounds in clinical applications. Graphical Abstracts